Stigma, Social Support, Illicit Drug Use, and Other Predictors of Anxiety and Depression Among HIV/AIDS Patients in Pakistan: A Cross-Sectional Study - Ahmed, Ali; Saqlain, Muhammad; Umair, Malik Muhammad; Hashmi, Furqan Khurshid; Saeed, Hamid; Amer, Muhammad; Blebil, Ali Qais; Dujaili, Juman Abdulelah (Frontiers in Public Health, 2021)
Introduction: Anxiety and depression in people living with HIV/AIDS (PLWHA) can lead to non-adherence to antiretroviral therapy (ART), morbidity, and mortality. Therefore, assessing the stigma, social support, and other determinants of anxiety and depression in PLWHA are important for developing further interventions. Methods: An institution-based cross-sectional study was conducted in 505 PLWHA, approached through systematic sampling, who paid routine visits to the antiretroviral therapy centre, Pakistan Institute of Medical Sciences (PIMS), Islamabad. Data was collected by pretested validated hospital anxiety and depression (HADS) scale. Version 26 of the SPSS was used to apply Logistic regression analysis to identify determinants, and the 95% confidence interval (CI) adjusted odds ratio (AOR) was calculated to assess the magnitude of the relationships. Results: In PLWHA, the prevalence of co-morbid depression and anxiety was 80%. Separately, 89.9% had depression, and 80.3% had anxiety. Use of illicit drugs (AOR = 1.87, 95% CI (1.01, 3.27)), low social support (AOR = 1.21, 95% CI (1.02, 2.25)), being male (AOR = 2.21, 95% CI (1.11, 5.49)) and HIV related stigma (AOR = 2.48, 95% CI (1.25, 6.02)) were significant predictors of depression. Having detectable viral load (AOR = 3.04, 95% CI (1.04, 8.86)), young age (AOR = 5.31, 95% CI (1.19, 29.39)), no formal education (AOR = 21.78, 95% CI (4.03, 117.62)), low (AOR = 1.70, 95% CI (1.12, 6.93)) or moderate (AOR = 2.20, 95% CI (1.79, 6.09)) social support, illicit drugs addiction (AOR = 1.17, 95% CI (1.03, 2.55)) and HIV stigma (AOR = 54.3, 95% CI (21.20, 139.32)) had a remarkable association with anxiety. Conclusions: Given the high prevalence of anxiety and depression among PLWHA, the Pakistan Ministry of Health should focus more on monitoring mental health, expanding mental health services, and developing interventions based on identified factors to treat depression and anxiety among PLWHA.